PENGEMBANGAN MEDIA PEMBELAJARAN HANDOUT AKUNTANSI KEUANGAN BERBASIS ANDROID GUNA MENDUKUNG PENDIDIKAN ERA SOCIETY 5.0 - Nazah Dwi Putricia; Khoirina Arsyanti; Nasywa Dellia Puteri; Amirul Arif; Luqman Hakim (Jurnal Genta Mulia, 2025)
The use of technology in education continues to grow, especially in supporting Society 5.0 era education which adopts digital means. This study aims to develop Android-based learning media for Financial Accounting subjects on the learning outcomes of the Petty Cash Fund in class XI SMK NU Bahrul Ulum Menganti. This learning media is designed in an android-based flipbook format so that it is easily accessible anytime and anywhere by students. This research uses the Research and Development (R&D) method with the ADDIE model which includes five stages: Analysis, Design, Development, Implementation, and Evaluation. Data collection techniques using tests, observations, and interviews. The data analysis technique uses material, language and media feasibility analysis. The results of validation by experts showed a very high feasibility level of 87% which stated that this media was valid in terms of content, language, and interactivity design. The results of the analysis of responses by teachers and students also showed a very practical category. Thus, this Android-based learning media can be an innovative solution to improve the effectiveness of learning Financial Accounting.